Characterization of the VVV survey RR lyrae population across the southern galactic plane - Minniti, Dante; Dékány, István (The astronomical journal, 2017)
Deep near-IR images from the VISTA Variables in the Vía Láctea (VVV) Survey were used to search for RR Lyrae stars in the Southern Galactic plane. A sizable sample of 404 RR Lyrae of type ab stars was identified across a thin slice of the fourth Galactic quadrant (295° < ℓ < 350°, −2.°24 < b < −1.°05). The sample’s distance distribution exhibits a maximum density that occurs at the bulge tangent point, which implies that this primarily Oosterhoff type I population of RRab stars does not trace the bar delineated by their red clump counterparts. The bulge RR Lyrae population does not extend beyond ℓ ∼ 340°, and the sample’s spatial distribution presents evidence of density enhancements and substructure that warrants further investigation. Indeed, the sample may be employed to evaluate Galactic evolution models, and is particularly lucrative since half of the discovered RR Lyrae are within reach of Gaia astrometric observations.
Gesehen am 20.10.2017